Detection of Hydrolyzed Fumonisins B1 and B2 by Use of High Performance Liquid Chromatography in Sorghum - SHARMA, MANJU (Asian Journal of Chemistry, 2010)
Fumonisins are a family of mycotoxins produced by Fusarium moniliforme and F. Proliferatum, two of the most prevalent fungal contaminants of maize, sorghum, millet and many other agricultural products. The most readily identifiable and toxicologically active metabolites of fumonisins B1 and B2 are hydrolyzed fumonisins B1 (HFB1) and B2 (HFB2). Quantification of these fumomsins in sorghum samples was done using reversed phase HPLC with fluorescence detection and OPA (o-phthaldialdehyde/2-mercaptoethanol) derivation method at λex 370/λex 418 nm. Detection limit was 20 ppb for both hydrolyzed fumonisins at a signal-to-noise ratio of 4 : 1. To the best of our knowledge this report appears to be the first study on the quantitative determination of HFB1 and HFB2 in naturally contaminated sorghum. HFB2 was absent in all the samples. In this study, the average hydrolyzed fumonisin B1 and B2 recoveries for four tested levels were 95.4% and 69.3% respectively. In conclusion, as corn is one of the major dietary staples for both animals and humans worldwide and many workers have reported their work on it, so there is need to study on the levels and production of fumonisins and their hydrolyzed moieties in sorghum also.